Новые памятники салтово-маяцкопо типа в окрестностях Керчи - Зинько, В.Н.; Пономарев, Л.Ю. (Материалы по археологии, истории и этнографии Таврии, 2000)
В последние десятилетия археологические исследования раннесредневековых памятников Восточного Крыма ведутся спорадически и бессистемно. В тоже время в ходе охранных раскопок, проводимых как в центре г. Керчи, так и в его окрестностях, открыты, подчас на значительных площадях, слои и погребения раннесредневекового времени. Особый интерес представляют памятники, оставленные сельским населением раннесредневекового Боспора. Some results of the research underteken by Bosporos rescue-archaeological expedition on the Chora of the ancient site of Nymphey in 1989 -1997. In the course of realizing the international scientific programme “Nymphey - history and structure of a Greek polis” complete research was carried out on the territory of more than 70 square kilometers. Due to this work the exact and detailed archaeological map of Nymphey Chora was drawn. Dozens of monuments of ttie Neolithic epoch. Bronze, Antiquity and Middle Ages were plotted on it.